Contracting the private health sector in Thailand's Universal Health Coverage. - Aniqa Islam Marshall; Woranan Witthayapipopsakul; Somtanuek Chotchoungchatchai; Waritta Wangbanjongkun; Viroj Tangcharoensathien (Public Library of Science (PLoS), 2023)
Private sector plays an import role in health service provision, therefore the engagement of private health facilities is important for ensuring access to health services. In Thailand, two of the three public health insurance schemes, Universal Coverage Scheme and Social Health Insurance, contract with private health facilities to fill gaps of public providers for the provision of health services under Universal Health Coverage. The National Health Security Office (NHSO) and Social Security Office (SSO), which manage the schemes respectively, have designed their own contractual agreements for private facilities. We aim to understand the current situation of contracting private health facilities within UHC of the two purchasing agencies. This qualitative descriptive case study was conducted through document review and in-depth interviews with key informants to understand how they contract private primary care facilities, service types, duration of contract, standard and quality requirement and renewal and termination of contracts. Private providers make a small contribution to the service provision in Thailand as a whole but they are important actors in Bangkok. The current approaches used by two purchasers are not adequate in engaging private sector to fill the gap of public provision in urban cities. One important reason is that large private hospitals do not find public contracts financially attractive. NHSO classifies contracts into 3 categories: main contracting units, primary care units, and referral units; while SSO only contracts main contracting units. Both allows subcontracting by the main contractors. Contractual agreements are effective in ensuring mandatory infrastructure and quality standards. Both purchasers have established technical capacities to enforce quality monitoring and financial compliance although there remains room for improvement especially on identifying fraud and taking legal actions. Contracting private healthcare facilities can fill the gap of public healthcare facilities, especially in urban settings. Purchasers need to balance the right level of incentives and accountability measures to ensure access to quality of care. In contracting private-for-profit providers, strong regulatory enforcement and auditing capacities are necessary. Further studies may explore various aspects contracting outcomes including access, equity, quality and efficiency impacts.